(3JMaI GdfHjg Ydi cJGH GdJfHjgs - (3GdRfcdhfjs; (3GdajQhRGHGOj GdTjQGRj , CHh ESMb EHQGgje Hf Ydj GdTjQGRj, CHh GSMGb , LeGd GdOjf,J (B476 (3g` s ((3MSf Hf eMeO Hf MSf s)
(3ChdgG (B:s
(3de JYJb Zf de jcf ESegG MQI fbd GdJUQjM Hg Yf GdbGVj s
(3BNQgG (B:s
(3HNdGa eG EPG cGf dg hdO aEf GdCe CMb Hg dCf KHhJ GdQb jefY ef ESJjdGFgG hGddg SHMGfg hJYGdi CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HgG ebGHdI ai BNQgG Ydi jO eGdcgG CMeO Hf YGHOjf YHOGdQMef GdYSbdGfj GdHHdHjSjs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3Gdabg GdTGaYjs